Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Live music by Legal Tender: Dave Maybary on saxophone, Nano Talanoa and Bob Fishman on guitar, Lorraine Bolen and Hal Bolen singing and drums, John B. Smith on keyboard, Tom Richey on guitar